Optimizing the number of blood cultures for lower and middle income countries: a large scale study in a public sector tertiary care teaching hospital of Southern India - Dhandapani, Sarumathi; Priyadarshi, Ketan; Sastry, Apurba Sankar (International Journal of Research in Medical Sciences, 2023)
Background: Blood culture is widely accepted as the gold standard investigation for the diagnosis of blood stream infections (BSI). The number of blood cultures collected has a considerable impact on the organism isolation. This study aims to optimize the number of blood cultures needed, for an optimal diagnostic yield in BacT/ALERT VIRTUO system mainly in a resource limited setting. Methods: All the blood cultures (BCs) obtained in BacT/Alert bottles per patient during a 24-h period were included as ‘one episode’ and categorized as single bottle, 1-set (2 aerobic bottles), 2 sets and 3 sets. BC bottles were incubated in the BacT/ALERT VIRTUO (bioMérieux) for a period of five days. Bottles flagged positive were subjected to Gram staining and culture plating. Colonies grown were identified by MALDI-TOF MS, VITEK MS, bioMérieux. Results: Cumulative positivity rate increased (21.7%, 41.4%, 56.1%, 60.6%) and pathogen isolation rate increased (10.3%, 21.8%, 30.4% and 33.8%) progressively when collected in single bottle, 1, 2 and 3 sets respectively. The pathogen detection rate for GNB and GPC were 45.1% and 42.6% respectively with one bottle and this got upsurged to 85.6% and 98.9% for GNB and 83.6% and 98.2% for GPC when collected in ≤1 set and ≤2 sets respectively. Conclusions: Two BC sets over a 24-h period can detect approximately 98% of the pathogens with a cumulative positivity rate of 60% and hence it is a justifiable alternative approach to the standard practice of 3-sets of BCs.